Gambaran Kesesuaian Intensitas Pencahayaan Ruang Kelas - Al'Fiqri, Ramadhan; Hapis, Abul Ainin; Harahap, Putri Sahara (Lontara Journal of Health Science and Technology, 2024)
Doing everything related to room activities, adequate lighting is needed, for a building required sufficient lighting intensity. The purpose of research to determine the intensity of room lighting.This research is a comparative descriptive research. This research was conducted at Campus X Jambi. The research sample was lighting intensity of 10 calssrooms. Sampling was carried out by direct measurement and then processed by comparison with applicable standards.it is known that there is no conformity in all classrooms after measuring the light intensity. Suggested to campus increase the number of lights and open the windows and doors while conducting lectures.